THE EFFECTIVENESS OF FINANCIAL ACCOUNTING STANDARDS IN IMPROVING THE QUALITY OF FINANCIAL REPORTS BAZNAS PAREPARE CITY - Putri, Najwa (Funds: Jurnal Ilmiah Akuntansi, Keuangan, dan Bisnis, 2025)
This study aims to determine how financial reports are presented at BAZNAS Parepare City and to evaluate the effectiveness of the implementation of Financial Accounting Standards (SAK) in improving accountable and transparent financial reporting. The research method used in this study is a case study with a qualitative approach, including in-depth interviews, observation of the financial recording and reporting process, and analysis of financial report documentation. The results of the study indicate that the structure and content of BAZNAS Parepare City financial reports still encounter several obstacles, including limited human resources who understand the standards in depth, inconsistencies in recording restricted and unrestricted funds, and a suboptimal accounting information system. In addition, the implementation of training and socialization regarding PSAK 109 still needs to be improved to support reporting effectiveness. The novelty of this study lies in its specific focus on the implementation and effectiveness of Financial Accounting Standards (SAK) in BAZNAS financial reports at the city level, namely BAZNAS Parepare City, which until now has rarely been studied in depth. Unlike previous studies, which generally focused on the implementation of SAK in general or at national-scale entities, this study also provides an empirical overview of the extent to which SAK can improve transparency, accountability, and the quality of financial reporting of zakat institutions in Parepare City. The implications of this research are expected to provide concrete input for BAZNAS in other regions and regulators to strengthen policies and provide guidance on SAK implementation for better zakat governance.